The Problem of Self-Presentation in the Modern Literary Process (“Narrative about the Author” in E. Simonova’s Interviews) - Elena Aleksandrovna Selyutina (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2023)
This article explores a particular version of the narrative of personal stories, i.e., the “narrative about the author”, which is indicative for the analysis of writers’ reflection on their role in modern Russian-language literature. The article aims to determine the specifics of the “narrative about the author”, show that it is formed in public discourse and conditioned by the existence of a narrative framework (a question-and-answer form of an interview that demonstrates public expectations from the creator). Public self-reflection captures the process of self-identification and modeling of the myth of verbal creative work in modern times. The event of the “narrative about the author” is an important change, after which they were able to define themselves as a writer (to name themselves). The author uses methods of classical and postclassical narratology, as well as personological and narrative psychology in the study of the “narrative about the author”. The study reveals that the “narrative about the author” occupies a borderline position with respect to fictionality, the narrator is non-trivial, they are both inside the event and outside it, combining personal attitude with social, cultural, and other conventions adopted about authorship. The article considers the “narrative about the author” with reference to an interview with the Ural poet E. Simonova. The empirical basis of the study is the interviews she gave from 2019 to 2022. In her interviews, Ekaterina Simonova creates an image of a “little poet”, a socio-psychological construct created under the influence of changes in the symbolic status of poetry in modern times, whose components are non-exclusivity and inclusion into everyday life. Within the narrative and within the limits of one response, one sees the formulation of a position, and in the comments given in parentheses, its ironic interpretation. As a result, the author concludes that in the interview with E. Simonova, a myth develops about the writer as an “everyday”, ordinary person who is built on a strategy of ironic sincerity, which is consistent with the artistic narrative of her poetry.